Children's internal migration and subjective wellbeing of older parents left behind: Spiritual or financial support? - Lu, Ying; Lin, Yi-Yang; Qu, Jun-Qiao; Zeng, Yi; Wu, Wan-Zong (Frontiers in Public Health, 2023)
Introduction Against the background of population aging and large-scale internal migration, this study uses an ordered logit with two-way fixed effects to examine the effect of children's internal migration on the subjective wellbeing of parents left behind. The study is based on the China Family Panel Studies database. Methods Data were obtained from CFPS (China Family Panel Studies), and ordered logit with two-way fixed effects was used to test the total effect of children's internal migration on subjective wellbeing of parents left behind, and KHB test was used to separate intergenerational spiritual support and intergenerational financial support to examine the intergenerational support preferences of parents left behind. Results The results show that children's internal migration has a significant negative effect on the subjective wellbeing of parents left behind, mainly through the reduction of intergenerational spiritual support. Furthermore, intergenerational financial support significantly mitigates this negative effect. There is heterogeneity in the direction of the total wellbeing effect across parents' preferences, as well as in the masking effect of financial support. However, the effect of financial support never fully offsets the effect of spiritual support. Discussion To cope with the negative effects of children's internal migration on parents, positive measures should be taken to change parental preferences.